Variability Studies of Two Prunus-Infecting Fabaviruses with the Aid of High-Throughput Sequencing - Koloniuk, Igor; Sarkisova, Tatiana; Petrzik, Karel; Lenz, Ondřej; Přibylová, Jaroslava; Fránová, Jana; Špak, Josef; Lotos, Leonidas; Beta, Christina; Katsiani, Asimina; Candresse, Thierry; Maliogka, Varvara I (Viruses, 2018)
During their lifetime, perennial woody plants are expected to face multiple infection events. Furthermore, multiple genotypes of individual virus species may co-infect the same host. This may eventually lead to a situation where plants harbor complex communities of viral species/strains. Using high-throughput sequencing, we describe co-infection of sweet and sour cherry trees with diverse genomic variants of two closely related viruses, namely prunus virus F (PrVF) and cherry virus F (CVF). Both viruses are most homologous to members of the Fabavirus genus (Secoviridae family). The comparison of CVF and PrVF RNA2 genomic sequences suggests that the two viruses may significantly differ in their expression strategy. Indeed, similar to comoviruses, the smaller genomic segment of PrVF, RNA2, may be translated in two collinear proteins while CVF likely expresses only the shorter of these two proteins. Linked with the observation that identity levels between the coat proteins of these two viruses are significantly below the family species demarcation cut-off, these findings support the idea that CVF and PrVF represent two separate Fabavirus species.
Keywords: High-Throughput Nucleotide Sequencing; genom virový; Genetic Variation; nemoci rostlin; Genome, Viral; Gene Expression Profiling; Prunus; slivoň; genetická variace; stanovení celkové genové exprese; vysoce účinné nukleotidové sekvenování; Plant Diseases; Fabavirus